Kesesuaian Pengelolaan Staf Mengacu Standar Internasional di Instansi Pelayanan Kesehatan Primer Kecamatan Borobudur dalam Mendukung Program Kawasan Strategis Pariwisata Nasional - Pangestuti, zashah Anisa; Kamal, sodiq; Hidayah, Nurul (Universitas Muhammadiyah Magelang, 2023)
Introduction: Health service facilities are a basic right of the community that must be fulfilled in the development of health and the degree of health in the community is influenced by the state of the facilities and facilities for health services. Health service facilities that are used to serve public health are promotive, preventive, curative and rehabilitative. The provision of health services can be influenced by adequate staff management so as to improve and maintain the health status of tourists. Objective: This research is aims to determine the suitability of staff management referring to international standards of primary health care agencies in Borobudur District in supporting the National Tourism Strategic Area program. Method: The method used is descriptive method with the number of subjects 50 people with the Total Sampling method. The data obtained were tested using IBM Statistics 21 for Windows. The measuring instrument used is the Staff Qualifications And Education Questionnaire. Result: The results showed that most of the staff had experience at the fullmet level as much as 62% in accordance with Joint Commission Internasional (JCI) standards covering aspects of planning, health and safety staff, medical staff, nursing staff and other professional staf